The manipulative function of prosodic interactive operators - Grzegorzewska, Anita (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
Among the studies on the class of manipulative phenomena, there are no works explaining the influence of prosody on the process of setting the manipulative sense of messages. Referring to the methodological assumptions developed within communicativism, the author researches the manipulative role of interactive operators appearing in the form of suprasegmental (stress, intonation) and segmental (pause) elements.   Influencing the audience with using the sound layer of the statement belongs to manipulative tricks when two conditions are met: the manipulator uses prosody fully intentionally to control the emotions, thoughts and behaviour of the recipient; listener is manipulated not entirely consciously or completely unconsciously.